2021
DOI: 10.1111/jce.15247
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and predictors of readmission after implantation of a percutaneous left atrial appendage occlusion device in the United States: A propensity score‐matched analysis from The National Readmission Database

Abstract: Background: Left atrial appendage occlusion (LAAO) devices have become a favorable alternative option among nonvalvular atrial fibrillation (AF) patients with long-term contraindication to anticoagulation. Real-world experience with postprocedural readmission rates and predictors of readmission in LAAO patients is limited.Objective: To assess all-cause 30-day readmission rate and predictors of readmission after LAAO procedure in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The observed 8.2% readmission rate at 30 days is slightly lower than that reported in previous studies, in which the overall 30-day readmission rate was 9.4%. 16 , 17 Moreover, the rates were lower than those reported for other catheter-based cardiac procedures, including catheter ablation for atrial fibrillation (11%), 18 , 19 transcatheter aortic valve implantation (11%), 20 and transcatheter edge-to-edge mitral valve repair (14%-16%). 21 , 22 …”
Section: Discussionmentioning
confidence: 81%
“…The observed 8.2% readmission rate at 30 days is slightly lower than that reported in previous studies, in which the overall 30-day readmission rate was 9.4%. 16 , 17 Moreover, the rates were lower than those reported for other catheter-based cardiac procedures, including catheter ablation for atrial fibrillation (11%), 18 , 19 transcatheter aortic valve implantation (11%), 20 and transcatheter edge-to-edge mitral valve repair (14%-16%). 21 , 22 …”
Section: Discussionmentioning
confidence: 81%
“…An amount of 125 patients (15.5%) died within the first year of LAAC in the study of Mesnier et al In the multivariable analysis, a factor associated with early death after LAAC was older age (HR: 1.03; 95% CI: 1.01–1.06 per year; p = 0.01) [ 30 ]. In addition, one study concluded that advanced age is associated with readmission after LAAC [ 31 ]. We also calculated the prevalence of comorbid conditions, such as coronary artery disease, congestive cardiac failure, and diabetes mellitus, between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology of identifying patients undergoing LAAO implantation and catheter-directed AF ablation from administrative databases has been adopted and validated in previous studies. 5 , 6 Our population of interest were patients undergoing LAAO + CA on the same day: therefore, patients undergoing LAAO or CA on different days during the same hospitalization were excluded (unweighted n = 23). Additionally, patients hospitalized in December were excluded (unweighted n = 78).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the use of left atrial appendage occlusion (LAAO) devices, such as the Watchman® device (Boston Scientific) and the Amulet® device (Abbott), has increased significantly in the USA 5 with lower in-hospital mortality and rehospitalization rates compared with matched AF cohorts. 6–8 LAAO is proven to reduce haemorrhagic stroke risk when compared with warfarin among non-valvular AF patients. 9–12 Combining AF ablation and implantation of LAAO device is expected to provide additive benefits in non-pharmacologic AF management.…”
Section: Introductionmentioning
confidence: 99%